# (cosx*cosy-cotx)dx-(sinx*siny)dy=0

## Simple and best practice solution for (cosx*cosy-cotx)dx-(sinx*siny)dy=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so dont hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

## Solution for (cosx*cosy-cotx)dx-(sinx*siny)dy=0 equation:

Simplifying
(cosx * cosy + -1cotx) * dx + -1(sinx * siny) * dy = 0
Multiply cosx * cosy
(c2o2s2xy + -1cotx) * dx + -1(sinx * siny) * dy = 0
Reorder the terms:
(-1cotx + c2o2s2xy) * dx + -1(sinx * siny) * dy = 0
Reorder the terms for easier multiplication:
dx(-1cotx + c2o2s2xy) + -1(sinx * siny) * dy = 0
(-1cotx * dx + c2o2s2xy * dx) + -1(sinx * siny) * dy = 0
(-1cdotx2 + c2do2s2x2y) + -1(sinx * siny) * dy = 0
Multiply insx * insy
-1cdotx2 + c2do2s2x2y + -1(i2n2s2xy) * dy = 0
Multiply i2n2s2xy * dy
-1cdotx2 + c2do2s2x2y + -1di2n2s2xy2 = 0
Solving
-1cdotx2 + c2do2s2x2y + -1di2n2s2xy2 = 0
Solving for variable 'c'.
Factor out the Greatest Common Factor (GCF), 'dx'.
dx(-1cotx + c2o2s2xy + -1i2n2s2y2) = 0
Subproblem 1Set the factor 'dx' equal to zero and attempt to solve:
Simplifying
dx = 0
Solving
dx = 0
Move all terms containing c to the left, all other terms to the right.
Add '-1dx' to each side of the equation.
dx + -1dx = 0 + -1dx
Remove the zero:
0 = -1dx
Simplifying
0 = -1dx
The solution to this equation could not be determined.
This subproblem is being ignored because a solution could not be determined.
Subproblem 2Set the factor '(-1cotx + c2o2s2xy + -1i2n2s2y2)' equal to zero and attempt to solve:
Simplifying
-1cotx + c2o2s2xy + -1i2n2s2y2 = 0
Solving
-1cotx + c2o2s2xy + -1i2n2s2y2 = 0
The solution to this equation could not be determined.
This subproblem is being ignored because a solution could not be determined.
The solution to this equation could not be determined.`